PHENOMENA SIMILAR TO TSUNAMI IN RUSSIAN INTERNAL BASINS - Didenkulova I.I.; Pelinovsky E.N. (My University, 2006)
Descriptions and records of phenomena similar to tsunami in Russian internal basins: rivers, lakes, and artificial water supply reservoirs are collected. During a period of 400 years, nine events of such type were found, seven of which can be considered reliable. The collected material confirms the risk of tsunami and phenomena similar to tsunami in all water reservoirs and the necessity of informing the population about this hazard.
Keywords: TSUNAMI; INTERNAL BASINS; PALEOTSUNAMI